Romanian immigration in Spain: an urgent commentary after the romanian republic´s entry in the european union - Álvarez, Aurelia; Benlloch, Pablo (Migraciones. Publicación del Instituto Universitario de Estudios sobre Migraciones, 2014)
The recent incorporation of Romania and Bulgaria to the European Union which has become effective from January 1st 2007, concludes the long process involved in the sixth enlargement. Because of their volume and because Romanians are a recent group in Spain but one of increasing importance, it would have been desirable that the regulation of the transitory period would have been made with less improvisation and haste. The article tackles some of the problems and practical difficulties which are emerging not only in the application of the envisaged transitory measures,but because of the coming into force in Spain of the new legal regulation for citizens of the European Union.